Tribhuvana Viśvavidyālaya Kānūna Adhyayana Saṃsthāna paricaya pustikā : pramāṇa patra taha (Tribhuvana Viśvavidyālaya, Kānūna Adhyayana Saṃsthāna, 1978)
Handbook of general information and curricula of the Institute of Law, Tribhuvan University.